Mitigation of Open‐Circuit Voltage Losses in Perovskite Solar Cells Processed over Micrometer‐Sized‐Textured Si Substrates. (14th November 2022) - Farag, Ahmed; Fassl, Paul; Hu, Hang; Feeney, Thomas; Quintilla, Aina; Ruiz‐Preciado, Marco A.; Hempel, Wolfram; Bagrowski, Dominik; Noack, Philipp; Wattenberg, Bianca; Dippell, Torsten; Paetzold, Ulrich W.
Abstract: The recent development of solution‐processed perovskite thin films over micrometer‐sized textured silicon bottom solar cells enables tandem solar cells with power conversion efficiencies > 30%. Next to improved light harvesting, textured silicon wafers are the industrial standard. To achieve high performance, the open‐circuit voltage losses that occur when fabricating perovskite solar cells over such textures need to be mitigated. This study provides a practical guideline to discriminate and address the voltage losses at the interfaces as well as in the bulk of solution‐processed double cation perovskite thin films using photoluminescence quantum yield measurements. Furthermore, the origin of these losses is investigated via morphological, microstructural, and compositional analysis and present possible mitigation strategies. The guideline will be beneficial for scientists working on randomly textured surfaces and provides a deeper understanding on this timely research topic. Abstract : Processing perovskite solar cells onto micrometer‐sized pyramidal textures is a timely research topic. The potential reasons behind the various voltage losses that come along with processing perovskite thin films onto such textures are investigated in‐depth via compositional, microstructural, and morphological analysis. A step‐by‐step guidance is presented on how to mitigate these voltage losses.